Identification of Borax Content and Mold Contamination in Branded Ready-to-Fry Puli Crackers in Surabaya City - Durotun Nafisha Safir; Ratna Yulistiani; Luqman Agung Wicaksono (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2026)
Puli crackers are still reported to contain borax as an unauthorized food additive, posing potential risks to food quality and safety. This study aimed to determine the borax content, total mold count, physicochemical properties (moisture content, expansion volume, and breaking force), and sensory characteristics of branded packaged puli crackers marketed in Surabaya, Indonesia. A descriptive study with a cross-sectional design was conducted using laboratory analyses. A total of 20 branded packaged puli cracker samples were collected from cracker retail stores using a total sampling technique.The results showed that 100% of the samples tested positive for borax, with concentrations ranging from 20.14 to 113.87 ppm. The moisture content ranged from 9.01% to 13.62%. All samples complied with the Indonesian National Standard (SNI 01-4307-1996) for total mold count, with values ranging from <10 to 7.0 × 10² CFU/g. The expansion volume ranged from 148.78% to 1041.08%, while the breaking force ranged from 2.54 to 13.61 N. The microbiological quality of the samples met the national standard for mold contamination; however, borax was detected in all samples, indicating the continued illegal use of borax in branded packaged puli crackers marketed in Surabaya. Contribution to Sustainable Development Goals (SDGs):SDG 6: Clean Water and SanitationSDG 11: Sustainable Cities and CommunitiesSDG 13: Climate ActionSDG 15: Life on Land